Prevalence of Carotid Artery Atherosclerosis Plaque in Systemic Lupus Erythematosus in Hasan Sadikin Hospital Bandung in 2017-2018 - Irham Rasyid; Syarief Hidayat; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2019)
Background. Systemic Lupus Erythematosus (SLE) is an autoimmune disease involving many organs including the cardiovascular system such as accelerated atherosclerosis or premature atherosclerosis. Atherosclerotic plaque can cause coronary heart disease, ischemic stroke and peripheral arterial disease, which are the main causes of death in the world. The purpose of this study was to determine the prevalence of carotid artery atherosclerosis plaques in patients with SLE. Method. This research is a descriptive study with a cross-sectional design. Carotid artery atherosclerosis plaques in SLE patients were assessed by analysing results of carotid ultrasound examinations that were conducted in 2017-2018. The inclusion criteria of this study were SLE patients who had undergone carotid doppler ultrasound B mode examination on the carotid artery for the period of 2017-2018. The exclusion criteria in this study were SLE patients with a history of stroke, peripheral arterial disease, and significant coronary artery disease. Result. This study involved 88 SLE patients who met the inclusion criteria. Results showed that there were 10 SLE patients (11.4%) who had atherosclerotic plaques. SLE patients with atherosclerosis plaque were mostly in the age range of 35-44 years (16%) and 45-54 years (22.2%). There were 2 patients (15.3%) with atherosclerotic plaque from a total of 11 patients had high triglyceride levels (â‰¥150 mg/dL). Chi square analysis of lipid profiles (cholesterol, LDL, HDL, triglycerides) in patients with atheroclerotic plaque revealed not significant (p>0.05). These findings could be caused by several factors, such as the small number of samples in this study and the non-traditional factors in the formation of atherosclerotic plaque as well as other traditional factors Conclusion. The prevalence of carotid artery atherosclerosis plaques in patients with SLE in Dr. Hasan Sadikin General Hospital in 2017-2018 is 11.4%.